P4.116 Long-acting reversible contraceptive use and receipt of sexual health services among young women: implications for sti/hiv prevention. (8th July 2017) - Steiner, Riley; Pazol, Karen; Swartzendruber, Andrea L; Kramer, Michael R; Gaydos, Laurie; Sales, Jessica M
Abstract : Introduction: Long-acting reversible contraceptive (LARC) users may be less likely to receive recommended STI prevention services because these methods do not require routine clinic visits for continuation. We compared receipt of services between young women using LARC and other contraceptive methods or no method. Methods: Data were from the 2011–2015 U.S. National Survey of Family Growth, a cross-sectional, nationally representative survey. We categorised sexually-active women aged 15–24 years (n=2, 018) as: new LARC (initiated ≤12 months prior) or continuing LARC (initiated >12 months) users; moderately (pill, patch, ring, injectable) or less (condoms, withdrawal, diaphragm, rhythm) effective method users; or non-contraceptors. We examined differences in past year chlamydia (CT) testing, HIV testing, and sexual risk assessment (2013–2015 only) by contraceptive type using bivariate statistics and logistic models adjusted for age and race/ethnicity. Results: Overall, 41% had been tested for CT, 26% for HIV, and 64% had risk assessed. Compared to moderately effective method users, continuing LARC users had lower odds of HIV testing (18 vs. 30%; AOR=0.4, 95%CI=0.2–0.7) and risk assessment (51 vs. 74%; AOR=0.3, 95%CI=0.2–0.7), but there were no significant differences in CT testing or between new LARC users and moderately effective method users. Compared to less effective method users, there were no differences in service receipt for continuing LARC users; new LARC users had higher odds of CT testing (52 vs. 24%, AOR=1.8, 95% CI=1.0–3.4) but no other differences were observed. Relative to non-contraceptors, new (43 vs. 28%, AOR=2.0, 95%CI=1.1–3.5) and continuing (52 vs. 28%; AOR=2.8, 95%CI=1.6–5.1) LARC users had higher odds of CT testing, and new LARC users had greater odds of risk assessment (72 vs. 55%; AOR=2.4, 95%CI=1.0–5.7). Conclusion: Continuing LARC users may be less likely to receive recommended services compared to users of moderately effective methods. STI prevention should be incorporated in efforts to increase access to the full range of contraception.